2023
DOI: 10.1093/jme/tjad142
|View full text |Cite
|
Sign up to set email alerts
|

Egg hatching success is influenced by the time of thermal stress in four hard tick species

Oluwaseun M Ajayi,
Kennan J Oyen,
Benjamin Davies
et al.

Abstract: Ticks are blood-feeding arthropods responsible for the transmission of disease-causing pathogens to a wide range of vertebrate hosts, including livestock and humans. Tick-borne diseases have been implicated in significant economic losses to livestock production, and this threat will increase as these obligate parasites widen their geographical ranges. Similar to other ectotherms, thermal stress due to changing global temperatures has been shown to influence tick survival and distribution. However, studies on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 75 publications
1
4
0
Order By: Relevance
“…As previously seen with thermal tolerance (Ajayi et al, 2024), the developmental stage of the egg had a major effect on survival after water submersion. Submersion in water was detrimental even after a single day.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…As previously seen with thermal tolerance (Ajayi et al, 2024), the developmental stage of the egg had a major effect on survival after water submersion. Submersion in water was detrimental even after a single day.…”
Section: Discussionsupporting
confidence: 68%
“…This is critical as disturbing egg clusters reduces viability (Benoit et al, 2007;Yoder et al, 2012;Ramos et al, 2013). Furthermore, the egg stage, whether early or late in development, is important to stress tolerance (Ajayi et al, 2024), which was not previously examined in relation to water submersion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The egg stage cannot move to more favorable conditions, and exposure to high temperatures during the egg stage has been shown to increase mortality and reduce growth in subsequent development stages in insects (Potter et al, 2011). Among other insects, no differences in thermal tolerance were noted in the eggs of the tobacco hornworm, Manduca sexta (Potter & Woods, 2012) and there has been very little focus on this topic in other arthropod systems (Ajayi et al, 2023; Denlinger & Yocum, 2019; Harvey et al, 2020; Hilker et al, 2023). Our study revealed significant differences in the egg-hatching rates for Ae.…”
Section: Discussionmentioning
confidence: 99%
“…Another critical abiotic component that can impact the viability of Aedes eggs is fluctuations in temperature (Faull & Williams, 2015; C. L. Judson, 1960). Heat stress can lead to negative consequences, including increased egg and larvae mortality, reduced insect larval growth, and even impacts on subsequent adult stages (Ajayi et al, 2023; Bowler & Terblanche, 2008; Rocha et al, 2017). For example, temperatures exceeding 30°C negatively impacted the viability of Anopheles gambiae mosquito egg development (Goltsev et al, 2009; Impoinvil et al, 2007).…”
Section: Introductionmentioning
confidence: 99%